2019
DOI: 10.3762/bjoc.15.117
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly behaviors of perylene- and naphthalene-crown macrocycle conjugates in aqueous medium

Abstract: The synthesis of conjugates of perylene diimide (PDI) and naphthalene diimide (NDI) modified with two benzo-21-crown-7 ethers (B21C7) are herein described. Their self-assembly behavior in various solvents was investigated particularly in aqueous medium, due to the recently discovered hydrophilic properties of B21C7 crown macrocycle. An unexpected fluorescence quenching phenomenon was observed in the PDI-B21C7 macrocycle conjugate in chloroform. The detailed UV–vis absorption and fluorescence spectra of these P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…These studies demonstrated the correlation between the hydration of CEs and the cyclic topological effect and the implications of cation affinities for neutral polar surfaces in the Hofmeister series. There is still much to explore and accomplish in this field; 1) CEs decorated with diverse functional groups make it easier to create diverse functional building blocks (Shen et al, 2019), thus enabling numerous opportunities for designing novel supramolecular materials in water; 2) To date, investigations into the aqueous behaviors of Se-or Te-containing CEs are scarce. The intrinsic catalytic roles and redox-responsiveness of Se and Te compounds significantly expand the functional range of CEs via substitution of a chalcogen atom on the CE with Se or Te (Shang et al, 2021a;Shang et al, 2021b;Li et al, 2022); 3) Revealing the interactions between water, CEs, and ions can benefit applied areas such as anti-icing materials (Ge et al, 2022;Hu et al, 2022) and aqueous metal-ion batteries (Wang et al, 2020).…”
Section: Summaries and Perspectivesmentioning
confidence: 99%
“…These studies demonstrated the correlation between the hydration of CEs and the cyclic topological effect and the implications of cation affinities for neutral polar surfaces in the Hofmeister series. There is still much to explore and accomplish in this field; 1) CEs decorated with diverse functional groups make it easier to create diverse functional building blocks (Shen et al, 2019), thus enabling numerous opportunities for designing novel supramolecular materials in water; 2) To date, investigations into the aqueous behaviors of Se-or Te-containing CEs are scarce. The intrinsic catalytic roles and redox-responsiveness of Se and Te compounds significantly expand the functional range of CEs via substitution of a chalcogen atom on the CE with Se or Te (Shang et al, 2021a;Shang et al, 2021b;Li et al, 2022); 3) Revealing the interactions between water, CEs, and ions can benefit applied areas such as anti-icing materials (Ge et al, 2022;Hu et al, 2022) and aqueous metal-ion batteries (Wang et al, 2020).…”
Section: Summaries and Perspectivesmentioning
confidence: 99%
“…They can provide a chelating effect but they would be a bit flexible. In literature, polyethers such as 15‐Crown‐5, [18]‐azacrown, pentaoxa‐heptadecane, bis(4‐{2‐[2‐methoxy ethoxy]ethoxy}phenyl) and benzo‐21‐crown‐7 attached to perylene diimide fluorophore are known for complexation of Ba 2+ in CH 3 CN, alkali ions in CHCl 3 , Ca 2+ ions in CH 2 Cl 2 , Ag + ion and Pb 2+ or K + ions in CHCl 3 :CH 3 CN (1 : 1, v/v), respectively [26–30] . However, the polyethers attached to 1,8‐naphthalimide fluorophore for recognition of heavy metals ions in aqueous medium and as developers for fingerprint imaging are scarcely known [31,32] …”
Section: Introductionmentioning
confidence: 99%
“…In literature, polyethers such as 15-Crown-5, [18]-azacrown, pentaoxa-heptadecane, bis(4-{2-[2-methoxy ethoxy]ethoxy}phenyl) and benzo-21-crown-7 attached to perylene diimide fluorophore are known for complexation of Ba 2 + in CH 3 CN, alkali ions in CHCl 3 , Ca 2 + ions in CH 2 Cl 2 , Ag + ion and Pb 2 + or K + ions in CHCl 3 : CH 3 CN (1 : 1, v/v), respectively. [26][27][28][29][30] However, the polyethers attached to 1,8-naphthalimide fluorophore for recognition of heavy metals ions in aqueous medium and as developers for fingerprint imaging are scarcely known. [31,32] In continuation of our interest on π-conjugated imide chemistry for detection of Pd, Fe species and other heavy metal ions, [33][34][35][36][37][38][39][40] herein, we have synthesized pseudo-crown ether functionalized 1,8-naphthalimide (NHG) using literature procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Ertekin and Nadeem's group reported fluorescent fibrous membrane doped with PDI derivative containing bis(4‐{2‐[2‐methoxyethoxy]ethoxy}phenyl) for detection of Ag + ion [31] . Jin, Qi and co‐workers reported self‐assembly behaviour of PDI derivative containing benzo‐21‐crown ether at N‐imide positions [32] . Chen and Mullen groups reported dibenzocoronene tetracarboxdiimide containing benzo‐21‐crown‐7 for detection of Pb 2+ or K + ions in CHCl 3 :CH 3 CN (1 : 1, v/v) solution [33] …”
Section: Introductionmentioning
confidence: 99%